Genomic Perl : from bioinformatics basics to working code - Dwyer, Rex A. (Cambridge University Press, 2003)
There are many basic computational problems in molecular biology and this text gives concise, working programs to solve them using Perl. With minimal prerequisites, the author explains the biological background for each problem, develops a model for the solution, then introduces the Perl concepts needed to implement the solution. Perl code is provided on the accompanying CD.